PERFORMANCE OF SELECTED COCONUT VARIETIES/ HYBRIDS UNDER SEQUENTIAL COCONUT TODDY AND NUT PRODUCTION SCHEME OR SCTNP - M.I. Secretaria; R.M. Ebuna; S.S. Magat; J.N. Maravilla; G.A. Santos; G.B. Baylon (International Coconut Community, 2002)
The response to sequential coconut toddy and nut production (SCTNP) scheme of four coconut varieties/hybrids at PCA-Zamboanga Research Center, San Ramon, Zamboanga City showed that the dwarf x tall hybrids, Malayan red dwarf x Baybay tall (MRD x BAYT), Malayan red dwarf x Tagnanan tall (MRD x TAGT) and Catigan green dwarf x Laguna tall (CATD x LAGT) produced significantly higher toddy (495 – 699 li/tree/yr) and nut yield (143-169 nuts/tree/yr) compared to tall cultivar, ‘Laguna’ LAGT (364 li and 123 nuts per tree per year). Varietal difference in terms of the floral and vegetative characteristics of the coconut cultivar and hybrids contributed significantly to the differences in the sap/toddy and nut yields.